2017
DOI: 10.1016/j.bjoms.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Mammary analogue secretory carcinoma of the salivary glands: a diagnostic dilemma

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 Mammary analogue secretory carcinoma of the salivary glands: a diagnostic dilemma AbstractMammary analogue secretory carcinoma (MASC) is a recently identified salivary gland neoplasm that can mimic other salivary gland tumours such as acinic cell carcinoma and cystadenocarcinoma. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…In our screening for secretory carcinoma candidates, we noted that zymogen granule-poor tumors that were initially diagnosed as acinic cell carcinoma constituted the largest source of secretory carcinomas, as reported in previous studies [4][5][6][7][8][9][10][11][12][13][14]. Although secretory carcinoma is the disease entity most commonly mimicked by acinic cell carcinoma [2,38], we confirmed that secretory carcinoma had several distinct features.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our screening for secretory carcinoma candidates, we noted that zymogen granule-poor tumors that were initially diagnosed as acinic cell carcinoma constituted the largest source of secretory carcinomas, as reported in previous studies [4][5][6][7][8][9][10][11][12][13][14]. Although secretory carcinoma is the disease entity most commonly mimicked by acinic cell carcinoma [2,38], we confirmed that secretory carcinoma had several distinct features.…”
Section: Discussionsupporting
confidence: 84%
“…The histologic features of secretory carcinoma include a variety of architectural growth patterns, the presence of intracytoplasmic vacuoles, mucin-like and colloid-like eosinophilic secretions, and a lack of intracytoplasmic periodic acid-Schiff + (PAS + ) zymogen granules. Immunohistochemistry analyses have shown that most secretory carcinomas are positive for S100 and mammaglobin and negative for DOG1 [2,[4][5][6][7][8][9][10][11][12][13][14][15]. Secretory carcinoma reveals relatively frequent rates of lymph node metastasis in as many as 25% of cases at presentation [2].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Since then, more than 70 additional cases have been reported, 2 often in small series of 10 cases or fewer. 3 , 4 MASC are mostly located in the parotid region but can appear in any location of the head and neck region. 5 Patients at all age are affected, including children and young adults.…”
Section: Introductionmentioning
confidence: 99%
“… 6-10 MASC are considered to be of low-grade malignancy; however, high-grade transformation and aggressive clinical behaviour has been described. 3 , 6 , 11 , 12 The prognostic impact of MASC is not clear as yet, although evidence exists that MASC has a comparable prognosis to other (low-grade) salivary gland tumors. 1 , 13 MASC are mostly small tumours measuring typically only a few centimeters in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of secretory carcinoma of salivary glands (SCSGs), a recently-described rare malignant tumor, was introduced by Skálová et al in 2010 [1]. These tumors were originally classi ed as mammary analogue secretory carcinomas of salivary glands because their histomorphological and immunohistochemical features are similar to those of secretory carcinoma of the breast [2]. The updated World Health Organization (WHO) Classi cation of Head and Neck Tumors (4th edition, 2017) substituted secretory carcinoma for the previous mammary analogue secretory carcinoma designation [3].…”
mentioning
confidence: 99%